The dream café : lessons in the art of radical innovation / Duncan D. Bruce and Dr. Geoff Crook. - Bruce, Duncan D., 1957- (John Wiley & Sons, 2015)
"Get out of the office and dream! To keep your brand innovative you need to feed your creative spirit and the office is not the place to do that. So get out, disrupt and reimagine the status quo, get into a cafe and dream. Recreating the convivial, collaborative, creative world of the avant-garde the guys at The Dream Cafe have developed a fresh, new approach which is being used by major brands and businesses to great success. They create actual Dream Cafe locations - settings which encourage freedom of thought and collaboration. Explaining how space and process can be harnessed to produce the kind of unanticipated multicultural and interdisciplinary encounters that lead to unpredictable outcomes.Now, for the first time, the innovation consultants at The Dream Cafe have made their model and methods available to us all in this exciting new book. Focuses on the urgent need to enable major brand businesses to formulate, refine, and deliver the big brand idea that will disrupt and redefine the market Shows how to innovate and stand out by embracing risk and innovation Equal parts inspiration and practical implementation The concept covered is currently being used extensively by major global brands and companies "--